2017
DOI: 10.1097/mpg.0000000000001611
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Functional Connectivity Between the Hypothalamus and High‐order Cortical Regions in Adolescent Patients With Irritable Bowel Syndrome

Abstract: The hypothalamus plays a critical role in maintaining visceral homeostasis. Altered hypothalamus activation has been implicated in functional gastrointestinal disorders, including irritable bowel syndrome (IBS). One important aspect of homeostatic regulation is the cortical modulation of limbic and paralimbic subsystems, including the hypothalamus, which in turn affects the descending regulatory processes mediating visceral homeostasis. Using neuroimaging, we evaluated hypothalamus functional connectivity in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Patients with functional dyspepsia manifested altered functional connectivity (FC) in the amygdala and insula ( 15 , 16 ). Reduced FC between the hypothalamus and high-order cortical area was found in adolescent IBS patients ( 17 ). Compared to female healthy controls, female IBS patients showed altered FC of the dorsal anterior insular with the medial prefrontal cortex (MPFC) and precuneus ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with functional dyspepsia manifested altered functional connectivity (FC) in the amygdala and insula ( 15 , 16 ). Reduced FC between the hypothalamus and high-order cortical area was found in adolescent IBS patients ( 17 ). Compared to female healthy controls, female IBS patients showed altered FC of the dorsal anterior insular with the medial prefrontal cortex (MPFC) and precuneus ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…43,63 Previous research has shown the AMY was activated during visceral pain in adults with IBS and not in healthy controls, 65 and changes in hypothalamus FC with the AMY were observed in youth with IBS vs healthy youth undergoing nonpainful rectal distention. 41 AMY FC has also changed after treatment for other pediatric chronic pain conditions, such as CRPS 61 and migraine. 48 Of interest, the AMY is also associated with negative affect, hyperarousal, and stress, and FAPD are highly comorbid with anxiety and other emotional problems, 12,16,18,68 particularly in more persistent and severe cases.…”
Section: The Role Of the Amygdala In Pain Processingmentioning
confidence: 99%
“…In youth with chronic pain, the AMY is thought to play an important role in aspects of nociceptive processing [57; 61], including pain attention and anticipation of pain [40; 60]. Prior research has shown the AMY was activated during visceral pain in adults with IBS compared to healthy controls [62] and changes in hypothalamus FC with the AMY were observed in youth with IBS versus healthy youth undergoing non-painful rectal distention [38]. AMY FC has also changed following treatment for other pediatric chronic pain conditions, such as CRPS [58] and migraine [45].…”
Section: The Role Of the Amy In Pain Processingmentioning
confidence: 99%
“…In studies of adolescents with IBS that induced non-painful visceral sensations via rectal distention, increased activation in regions associated with nociceptive processing (e.g., insula) and emotional arousal (e.g., pACC) were observed [39]. Reduced hypothalamic FC was observed in brain regions associated with cognition (bilateral prefrontal cortices), memory (hippocampus) and emotion (AMY) [38]. However, there is presently a lack of understanding of the neural mechanisms of pediatric FAPD using non-invasive visceral pain induction methods.…”
Section: Introductionmentioning
confidence: 99%